Chrysanthemum Garden in Southern California - Fannie Eliza Duvall:::Artist:::::::::::: (2023)
Fannie Eliza Duvall - Chrysanthemum Garden in Southern California, 1891. This painting is used for the cover of The Chrysanthemums by John Steinbeck, Perfection Form Co, c.1979.